Adverse pregnancy outcomes by maternal anxiety disorder during pregnancy occurring with and without other mental health conditions: a retrospective cohort study - Rebecca J. Baer; Scott P. Oltman; Deborah Adeyemi; Ribka Amsalu; Kacie C. A. Blackman; Bridgette Blebu; Kimberly Coleman-Phox; Jennifer N. Felder; Dawn Gano; Audrey Lyndon; Safyer McKenzie-Sampson; Carolyn Ponting; et al. (Reproductive Health, 2026)
Abstract Background Anxiety disorders during pregnancy are common. Understanding whether the presence of anxiety with comorbid mental health conditions confers an increased risk to pregnant people and their infants is understudied. Methods The sample included singleton liveborn infants in California from 2007–2020. Mental health conditions during pregnancy were obtained from discharge records. Adverse pregnancy outcomes examined included placental abruption, severe maternal morbidity (SMM), small or large for gestational age infant, preterm birth, or early term birth. Relative risks and 95% confidence intervals for each adverse outcome were estimated using modified Poisson regression with a log link and robust sandwich standard errors for people with an anxiety disorder diagnosis versus people without a mental health diagnosis. Calculations were made for people with any anxiety disorder, anxiety disorder only, anxiety disorder with comorbid depression, anxiety disorder with a comorbid non-depression mental health diagnosis, and anxiety disorder with comorbid depression and another mental health diagnosis. Four different models were considered: 1) unadjusted, 2) adjusting for racial/ethnic group, education, insurance, participation in Special Supplemental Nutrition Program for Women, Infants, and Children (WIC), adequacy of prenatal care, age, and parity, 3) adjusting for model two plus infection, smoking, and drug/alcohol use, and 4) adjusting for model three plus diabetes and hypertension. Results Of 5,836,541 maternal-infant pairs, 2.2% pregnant people had an anxiety disorder diagnosis during their pregnancy or at the birth admission. Of those with anxiety, 29.4% had a comorbid mental health diagnosis. People with an anxiety disorder during pregnancy were at increased risk of nearly all the adverse pregnancy outcomes examined. In fully adjusted models, individuals with anxiety and depression were 1.7-times more likely to have a provider-initiated birth before 32 weeks and were 1.5-times more likely to have SMM. Conclusion Maternal anxiety disorder diagnosis during pregnancy was associated with an elevated risk of an adverse pregnancy outcome even after adjustment for maternal factors. Rates of adverse outcomes were higher among individuals with a comorbid mental health diagnosis than those with an anxiety disorder alone. These findings indicate that individuals with anxiety disorders are at increased risk of adverse pregnancy outcomes, highlighting the importance of prioritizing mental health support during pregnancy.